Epidemic Trade - Lars Boerner; Battista Severgnini (European Historical Economics Society (EHES), 2012)
This paper studies the spread of the Black Death as a proxy for the intensity of medieval trade ows between 1346 and 1351. The Black Death struck most areas of Europe and the wider Mediterranean. Based on a modi ed version of the gravity model, we estimate the speed (in kilometers per day) of transmission of the disease between the transmitting and the receiving cities. We find that the speed depends on distance, political borders, and on the political impor- tance of a city. Furthermore, variables related to the means of transportation like rivers and the sea, religious seasons such as Advent, and geographical position are of substantial significance. These results are the rst to enable us to identify and quantify key variables of medieval trade ows based on an empirical trade model. These results shed new light on many qualitative debates on the importance and causes of medieval trade.Length: 40 pages
Keywords: F10; F15; N13; 330; Trade; Middle Ages; Black Death; Gravity model; Poisson regression